Left breast irradiation with tangential intensity modulated radiotherapy (t-IMRT) versus tangential volumetric modulated arc therapy (t-VMAT): Trade-offs between secondary cancer induction risk and optimal target coverage - Karpf, Daniel; Sakka, Mazen; Metzger, Martin; Grabenbauer, Gerhard G. (Radiation Oncology, 2019)
Background: Adjuvant radiotherapy is the standard treatment after breast-conserving surgery. According to meta-analyses, adjuvant 3d-conventional irradiation reduces the risk of local recurrence and thereby improves long-term survival by 5-10%. However, there is an unintended exposure of organs such as the heart, lungs and contralateral breast. Irradiation of the left breast has been related to long-term effects like increased rates of coronary events as well as second cancer induction. Modern radiotherapy techniques such as tangential intensity modulated radiotherapy (t-IMRT) and tangential volumetric modulated arc therapy (t-VMAT) and particularly deep inspiration breath hold (DIBH) technique have been developed in order to improve coverage of target volume and to reduce dose to normal tissue. The aim of this study was to compare t-IMRT-plans with t-VMAT-plans in DIBH position for left-sided breast irradiation in terms of normal tissue exposure, i.e. of lungs, heart, left anterior descending coronary artery (LADCA), as well as homogeneity (HI) and conformity index (CI) and excess absolute risk (EAR) for second cancer induction for organs at risk (OAR) after irradiation. Methods: Twenty patients, diagnosed with left-sided breast cancer and treated with breast-preserving surgery, were included in this planning study. For each patient DIBH-t-IMRT plan using 5 to 7 beams and t-VMAT plan using four rotations were generated to achieve 95% dose coverage to 95% of the volume. Data were evaluated on the basis of dose-volume histograms: Cardiac dose and LADCA (mean and maximum dose, D25% and D45%), dose to ipsilateral and contralateral lung (mean, D20%, D30%), dose to contralateral breast (mean dose), total monitor units, V5% of total body and normal tissue integral dose (NTID). In addition, homogeneity index and conformity index, as well as the excess absolute risk (EAR) to estimate the risk of second malignancy were calculated. Results: T-IMRT showed a significant reduction in mean cardiac dose of 26% (p = 0.002) compared to t-VMAT, as well as a significant reduction in the mean dose to LADCA of 20% (p = 0.03). Following t-IMRT, mean dose to the left lung was increased by 5% (p = 0.006), whereas no significant difference was found in the mean dose to the right lung and contralateral breast between the two procedures. Monitor units were 31% (p = 0.000004) lower for t-IMRT than for t-VMAT. T-IMRT technique significantly reduced normal tissue integral dose (NTID) by 19% (p = 0.000005) and the V5% of total body by 24% (p = 0.0007). In contrast, t-VMAT improved CI and HI by 2% (p = 0.001) and 0.4% (p = 0.00001), respectively. EAR with t-IMRT was significantly lower, especially for contralateral lung and contralateral breast (2-5/10,000 person years) but not for ipsilateral lung. Conclusion: Compared to t-VMAT, t-IMRT in left-sided breast irradiation significantly reduced dose to organs at risk as well as normal tissue integral dose, and V5% total body. EAR with t-IMRT was significantly lower for contralateral lung and contralateral breast. T-VMAT, however, achieved better homogeneity and conformity. This may be relevant in individual cases where sufficient coverage of medial lymphatic target volumes is warranted.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Breast cancer; Cardiac dose; Deep inspiration breath hold; Homogeneity index (HI) and conformity index (CI); Tangential intensity modulated radiotherapy (t-IMRT); Tangential volumetric modulated arc therapy (t-VMAT). Normal tissue integral dose (NTID)